THE EFFECTIVENESS OF COOPERATIVE LEARNING IN THE COURSE OF MATHEMATIC PROBLEM SOLVING - Suryatin Suryatin (Indonesian Journal of Elementary Teachers Education, 2020)
Problems in mathematics are a challenge that needs solving but the solution cannot be done by using routine procedures. Understanding the problem as well as wealth of experience and strategy is needed to solve these problems. Students need experiences that can be obtained through interaction with others in cooperative learning. Different strategies that may emerge from others can enrich their experiences. The study was conducted to determine the effectiveness of cooperative learning in mathematics problem solving courses. The research method used is descriptive qualitative research methods. The object of research is the effectiveness of group learning in mathematics problem solving courses which include four procedures: understanding problems, planning strategies, solving, and checking answers. The research subjects are fifth semester students of PGSD STKIP PGRI Pacitan study program in the academic year 2019/2020. Sources of data in this study are: (1) Mathematical problem solving test data (2) Observation data during the lecture process (3) Group learning questionnaire data. Test of validity of the data is done through triangulation technique. The results showed that group learning in mathematics problem solving courses had fulfilled the characteristics of cooperative learning, providing benefits to students. And the effectiveness of four mathematical problem-solving procedures resulted in 80% for problem understanding, 80% for strategic planning, 70% for solving math problems, and 75% for checking math problem solving.Keywords: mathematical problem solving; cooperative learning; mathematics.